The use of antiplatelet agents after an acute coronary syndrome in a large community Italian setting of more than 12 million subjects. Issue 6 (1st September 2019) - Maggioni, Aldo P; Dondi, Letizia; Pedrini, Antonella; Ronconi, Giulia; Calabria, Silvia; Cimminiello, Claudio; Martini, Nello
Abstract: Background: Antiplatelet agents are the cornerstone of medical treatment in acute coronary syndromes. The aim of this study was to evaluate the clinical epidemiology of patients after an acute coronary syndrome treated with different antiplatelet agent regimens in a large real community setting. Methods: The ARCO database, including more than 12 million inhabitants, was evaluated. Antiplatelet agent prescriptions were analysed as follows: aspirin, clopidogrel, other antiplatelet agents used alone; the free and fixed combination of clopidogrel and aspirin; the free combination of aspirin with other antiplatelet agents. Healthcare costs included drug prescriptions (prices reimbursed by the Italian National Health System), outpatient specialist services and hospitalisations (Italian national tariffs). Results: From 1 January to 31 December 2014, 26, 834 patients were discharged after an acute coronary syndrome. Of these, 19, 333 (77%) were prescribed with an antiplatelet agent. Among patients undergoing a revascularisation procedure either percutaneous or surgical (47% of the total population), antiplatelet agents were prescribed in 90% of cases. Dual antiplatelet agent therapy was prescribed in 49.6% of the total population and in 68.5% of those treated invasively. Prescription continuity was observed in just 75% of patients. The highest adherence was observed for the fixed combination of aspirin/clopidogrel (81.5%). Throughout one year of follow-up re-hospitalisation occurred in 47.9% of the patients and the direct cost per patient treated with an antiplatelet agent was €13, 297 versus €16, 647 in patients not treated with antiplatelet agents. Conclusions: This study highlights that antiplatelet agent prescriptions, specifically dual antiplatelet agent therapy, are at least suboptimal as well as in prescription continuity. Hospitalisations were frequent and were the main driver of the costs, accounting for 84% of the total costs for the Italian National Health System.